Gambaran Higiene Penjual, Sanitasi Tempat Potong Ayam dan Keberadaan Escherichia Coli pada Daging Ayam: Studi Kasus Pada Penjual Ayam Potong di Beberapa Pasar di Wilayah Kota Kupang - Virginia P. Daka; Luh Putu Ruliati; Soni Doke (Yayasan Literasi Sains Indonesia, 2024)
Chicken meat has many nutrients that make chicken meat the right medium for the proliferation of bacteria, Personal hygiene and sanitation of chicken slaughterhouses that are not good can cause chicken meat to become a medium for transmitting diseases caused by food, bacteria, one of which is Escherichia coli which often contaminates chicken meat. So this study aims to determine the description of the hygiene of the seller, the sanitation of the chicken slaughterhouse and the presence of Escherichia coli in chicken meat, a case study of slaughtered chicken sellers in several markets in the Kupang City area. This type of research is quantitative descriptive research. The research was conducted in Pasar Inpres, Pasar Oeboba and Pasar Oeba in Kupang City from January to February 2024. The population of this study were all chicken meat sellers in Inpres Market, Oebobo Market and Oeba Market in Kupang City with a total of 40 workers, the sample in this study amounted to 40 chicken meat samples and there were 40 hygiene, sanitation data. The instruments used were questionnaires and laboratory tests. The results of this study showed personal hygiene that there were 27 respondents (67,5%) who did not meet the requirements and 13 respondents (32,5%) who met the requirements, sanitation results that there were 37 respondents (92,5%) who did not meet the requirements and 3 respondents (7,5 %) who met the requirements, Escherichia coli results that did not meet the requirements of 40 sellers (100%).